Descriptive epidemiology of physical activity energy expenditure in UK adults (The Fenland study) - Tim Lindsay; Kate Westgate; Katrien Wijndaele; Stefanie Hollidge; Nicola Kerrison; Nita Forouhi; Simon Griffin; Nick Wareham; Søren Brage (BMC, 2019)
Abstract Background Physical activity (PA) plays a role in the prevention of a range of diseases including obesity and cardiometabolic disorders. Large population-based descriptive studies of PA, incorporating precise measurement, are needed to understand the relative burden of insufficient PA levels and to inform the tailoring of interventions. Combined heart and movement sensing enables the study of physical activity energy expenditure (PAEE) and intensity distribution. We aimed to describe the sociodemographic correlates of PAEE and moderate-to-vigorous physical activity (MVPA) in UK adults. Methods The Fenland study is a population-based cohort study of 12,435 adults aged 29-64 years-old in Cambridgeshire, UK. Following individual calibration (treadmill), participants wore a combined heart rate and movement sensor continuously for 6 days in free-living, from which we derived PAEE (kJ•day− 1•kg− 1) and time in MVPA (> 3 & > 4 METs) in bouts greater than 1 min and 10 min. Socio-demographic information was self-reported. Stratum-specific summary statistics and multivariable analyses were performed. Results Women accumulated a mean (sd) 50(20) kJ•day− 1•kg− 1 of PAEE, and 83(67) and 33(39) minutes•day− 1 of 1-min bouted and 10-min bouted MVPA respectively. By contrast, men recorded 59(23) kJ•day− 1•kg− 1, 124(84) and 60(58) minutes•day− 1. Age and BMI were also important correlates of PA. Association with age was inverse in both sexes, more strongly so for PAEE than MVPA. Obese individuals accumulated less PA than their normal-weight counterparts, whether considering PAEE or allometrically-scaled PAEE (− 10 kJ•day− 1•kg− 1 or − 15 kJ•day− 1•kg-2/3 in men). Higher income and manual work were associated with higher PA; manual workers recorded 13-16 kJ•kg− 1•day− 1 more PAEE than sedentary counterparts. Overall, 86% of women and 96% of men accumulated a daily average of MVPA (> 3 METs) corresponding to 150 min per week. These values were 49 and 74% if only considering bouts > 10 min (15 and 31% for > 4 METs). Conclusions PA varied by age, sex and BMI, and was higher in manual workers and those with higher incomes. Light physical activity was the main driver of PAEE; a component of PA that is currently not quantified as a target in UK guidelines.